Development, quality, and influencing factors of colonoscopy in China: results from the national census in 2013 and 2020 - Jiao, Yun-Fei; Cheng, Zhi-Yuan; Gao, Ye; Yu, Chu-Ting; Jiang, Hui-Shan; Wang, Ting-Lu; Deng, Ying; Lin, Han; Wang, Tian-Jiao; Wang, Wei; Wan, Rong; Li, Zhao-Shen; et al. (Frontiers in Oncology, 2023)
With the increasing burden of colorectal cancer (CRC), the practice of colonoscopy is gaining attention worldwide. However, it exhibits distinct trends between developing and developed countries. This study aims to explore its development and identify influencing factors in China.The Chinese Digestive Endoscopy Censuses were conducted twice in mainland China under the supervision of health authorities. Information regarding the practice of colonoscopy was collected through a structured online questionnaire. The authenticity of the data was evaluated through logical tests, and a random selection of endoscopic reports underwent manual validation by Quality Control Centers. Potential factors associated with colonoscopy were analyzed using real-world information.From 2012 to 2019, the number of hospitals that performed colonoscopy increased from 3,210 to 6,325 (1.97-fold), and the volume increased from 5.83 to 12.92 million (2.21-fold). The utilization rate rose from 436.0 to 914.8 per 100,000 inhabitants (2.10-fold). However, there was an exacerbation of regional inequality in the adequacy of colonoscopy. Regions with higher incidence of CRC, higher gross domestic product per capita, more average numbers of endoscopists and tertiary hospitals tended to provide more accessible colonoscopy (P<0.001). Nationwide, the cecal intubation rate improved from 83.9% to 94.4% and the unadjusted adenoma detection rate (ADR) improved from 16.3% to 18.1%. Overall, hospital grading, educational background of endoscopists, economic income, and colonoscopy volume were observed as the significantly positive factors affecting ADR (P<0.05), but not the incidence of CRC or the number of endoscopists.Tremendous progress in colonoscopy has been made in China, but some issues needed timely reflection. Our findings provide timely evidence for better colonoscopy strategies and urgent measures, such as quality control and medical education of endoscopists..